Effective Altruism and Religion Synergies, Tensions, Dialogue - Roser, Dominic; Riedener, Stefan; Huppenbauer, Markus (Religion - Wirtschaft - Politik, 2022)
A new movement is on the scene: effective altruism-the combination of love and efficiency, making the world a better place not just with a bleeding heart and empathy but with a radical focus on reason and evidence and never losing sight of the goal of maximal impact. Its adherents typically stem from strongly secular environments such as elite philosophy departments or Silicon Valley. So far, a religious perspective on this movement has been lacking. What can people of faith learn from effective altruism, how can they contribute, and what must they criticise? This volume offers a first examination of these questions, providing both a Buddhist and an Orthodox Jewish perspective on them, in addition to various Christian contributions. With contributions by Calvin Baker, Lara Buchak, Mara-Daria Cojocaru, Stefan Höschele, Markus Huppenbauer, Robert MacSwain, David Manheim, Kathryn Muyskens, Stefan Riedener, Dominic Roser and Jakub Synowiec.